2020
DOI: 10.1021/acssensors.0c00270
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fluorescent Probes for Imaging and Evaluation of Hypochlorite Fluctuations during Diagnosis and Therapy of Osteoarthritis in Cells and in a Mouse Model

Abstract: The early diagnosis of osteoarthritis (OA) can halt or delay the progression of the disease, and it is essentially beneficial to its treatment. However, biomarkers with sufficient sensitivity for dynamically identifying early OA are still yet to be determined. The overproduced hypochlorous acid (HOCl) has been proposed as an obvious symptom in early OA. Herein, based on the oxidation reaction of the sulfur atom in phenothiazine into sulfoxide, we design and synthesize a phenothiazine-derived coumarin fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…10 Typically, the sulfur atom in phenothiazine could be oxidized into sulfoxide by HClO if an alkyl substituent is attached to the nitrogen atom of phenothiazine, which has been utilized to develop phenothiazine-based probes for HClO by Pu and other groups. 6,7,10,23,36 We found that the sulfur atom in the phenothiazine moiety was rapidly oxidized to sulfonium after being treated with HClO, then producing the phenothiazin-5-ium moiety with strong electron-withdrawing capability. Other previously reported reaction mechanisms for the detection of HClO were summarized in Table S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Typically, the sulfur atom in phenothiazine could be oxidized into sulfoxide by HClO if an alkyl substituent is attached to the nitrogen atom of phenothiazine, which has been utilized to develop phenothiazine-based probes for HClO by Pu and other groups. 6,7,10,23,36 We found that the sulfur atom in the phenothiazine moiety was rapidly oxidized to sulfonium after being treated with HClO, then producing the phenothiazin-5-ium moiety with strong electron-withdrawing capability. Other previously reported reaction mechanisms for the detection of HClO were summarized in Table S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 Although the etiology of RA is not fully elucidated, it is understood to be closely related to the overproduction of HClO in early RA. 9,10 To date, X-ray, computed tomography, ultrasonography, and magnetic resonance imaging (MRI) are being used for diagnostic imaging of RA in clinic. 11 However, these conventional imaging methods suffer from low sensitivity, poor spatiotemporal resolution, and danger of radiation for early diagnosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the reported benzopyrylium–coumarin fluorescent probes have only one recognition site that responds to both HClO and SO 2 , they are incapable of distinguishing HClO from SO 2 . ,, It is known that the phenothiazine moiety can selectively be oxidized by HClO; thus, it was applied in the design of the fluorescent probes for HClO. …”
Section: Resultsmentioning
confidence: 99%
“…As a typical soft material, supramolecular gels show smart response to external stimuli, [3][4][5] such as temperature, light, pH values and chemical reactions, leading to their wide application in the fields of biomedicine, flexible electronic equipment, water purification, sensing and recognition. [6][7][8][9][10] Considering that the sophisticated functions of organisms rely on highly ordered self-organizing systems and a series of chemical reactions, chemical reaction-guided supramolecular gelation would not only deepen our understanding of the organization of biomolecular systems, but also afford supramolecular materials with intriguing properties, such as adaptation and self-replication. [11][12][13] Furthermore, the reaction-guided diffusion of gelators would give spatially defined soft matter with concentration gradient or varied chemical compositions at different locations.…”
Section: Introductionmentioning
confidence: 99%